2015
DOI: 10.21608/mjvh.2015.4563
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis A virus infection in patients with chronic liver diseases: Do we need to vaccinate?

Abstract: Superinfection of patients with chronic liver disease (CLD) with hepatitis A virus (HAV) may have deleterious effects including hepatic decompensation HAV (OR: 5.2, p<0.001). Also, patients >20 years old, and those >40 years old had significantly more anti-HAV IgG seropositivity compared to those who are younger in age (OR: 11.4, p<0.0001 and OR: 3.8, p<0.01 respectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…This study showed that age had a significant direct association with HAV immunity. This finding is consistent with the studies by Shavakhi et al ( 14), Cho et al (18), and Helmy et al (19), which similarly found more immunity among older ones. Furthermore, the lower level of knowledge of transmission routes of HAV was correlated directly with immunity against HAV, which was in contrast to a study conducted by Lankarani et al in the general population (4).…”
Section: Discussionsupporting
confidence: 93%
“…This study showed that age had a significant direct association with HAV immunity. This finding is consistent with the studies by Shavakhi et al ( 14), Cho et al (18), and Helmy et al (19), which similarly found more immunity among older ones. Furthermore, the lower level of knowledge of transmission routes of HAV was correlated directly with immunity against HAV, which was in contrast to a study conducted by Lankarani et al in the general population (4).…”
Section: Discussionsupporting
confidence: 93%